Cf/C–SiC–MoSi2 composites with good ablation performance prepared via a two-step hydrothermal method. Issue 19 (16th February 2017) - Bai, Zhe; Cao, Liyun; Huang, Jianfeng; Ouyang, Haibo; Su, Jinbu; Li, Cuiyan; Fu, Ao
Abstract : Cf /C–SiC–MoSi2 composites were prepared via a simple hydrothermal method. Abstract : Cf /C–SiC–MoSi2 composites were prepared via a simple hydrothermal method. The kinetics of the hydrothermal penetration process, the mechanical properties, and ablation behaviors of the composites were investigated. Results showed that the penetration activation energy was only 51.3 kJ mol −1 . The flexural strength of the composites was 111.7 MPa. The Cf /C–SiC–MoSi2 composites exhibited good ablation properties after being exposed to plasma flame at 2300 °C. During the ablation, molten SiO2 could prevent carbon from oxidation. Moreover, the transformation from MoO2 to gaseous MoO3 consumed considerable amounts of oxygen and absorbed a large amount of heat, which prevented the composites from further ablation.